2022
DOI: 10.1029/2022ja030330
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Instrument Observations of the Ionospheric Response to the 26 December 2019 Solar Eclipse Over Indian and Southeast Asian Longitudes

Abstract: A solar eclipse is a rare astronomical event that occurs when the Sun, Moon, and Earth are aligned in a straight line with the moon in between the sun and earth occulting the Sun as well as its radiation by casting a shadow on different parts of the earth. Solar eclipse observation gives a unique opportunity to study the impact of solar radiation on the atmosphere-ionosphere coupled system. The effect of solar eclipses is noticed as a sudden decrease of ionospheric density due to the cutoff of solar ionizing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…The absence of the sandwich feature in the TECP data reveals some limitations in how much the inhomogeneous solar EUV illumination can directly modulate the ionosphere. Our findings on emergent features of wavelike perturbations in TEC data during the 26 December 2019 eclipse are consistent with Barad et al (2022), who found similar features from observations over the Indian region, while ours came from the Southeast Asian region and specifically over the Indonesian sector.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The absence of the sandwich feature in the TECP data reveals some limitations in how much the inhomogeneous solar EUV illumination can directly modulate the ionosphere. Our findings on emergent features of wavelike perturbations in TEC data during the 26 December 2019 eclipse are consistent with Barad et al (2022), who found similar features from observations over the Indian region, while ours came from the Southeast Asian region and specifically over the Indonesian sector.…”
Section: Discussionsupporting
confidence: 93%
“…In this paper, we investigated the ionospheric response to the 26 December 2019 annular solar eclipse event over the Indonesian sector using a combination of ionosonde and GNSS receiver observations, in conjunction with solar image analysis. The present work adds to existing analyses of this particular event performed independently by Aa et al (2020) and Barad et al (2022) over the Indian and Southeast Asian longitudes. Section 2 of this paper describes the methodology, Section 3 describes the observation results, Section 4 presents a discussion of the findings, and Section 5 presents the conclusion.…”
mentioning
confidence: 85%
“…To decipher gravity waves launched upward from the top of the cyclone we have used data from SABER (Sounding of the Atmosphere using Broadband Emission Radiometry). The SABER constitutes one of the instrumental components integrated into the TIMED (Thermosphere Ionosphere Mesosphere Energetics Dynamics) satellite (https://saber.gats-inc.com/browse_data.php) (e.g., Barad et al., 2022; Tikemani & Sivakumar, 2023). Our study exclusively employed data from SABER Version 2.0, spanning the period from 18 April to 11 May 2019 to include pre‐, post‐ and cyclone periods.…”
Section: Datamentioning
confidence: 99%
“…Previous experiments show a high electrical voltage in our atmosphere during an eclipse. The shadow of the eclipse can cause changes in the ionosphere that are significant enough to affect radio wave propagation and possibly human physiology (Wang et al, 2022;Barad, Sripathi and England, 2022;Das, Barman, Pal, & Haldar, 2022;Chernogor, Garmash, Guo, Luo, Rozumenko, & Zheng, 2020).…”
Section: Figure 1 Date Of Total Solar Eclipsementioning
confidence: 99%